ANALISIS KARAKTERISTIK ANTIOKSIDAN DALAM MISTER KUMIS: MINUMAN INSTAN SERBUK KULIT MANGGIS ( Gar c inia mangostana L) - Dwi Prihastuti, Ainun Afif, Laela Mukaro Nenny Widiani (Pelita - Jurnal Penelitian Mahasiswa UNY, 2012)
This research is aimed at finding out the antioxidant contents in instant drinkingpowder of mangosteen (Garcinia mangostana L) peel and finding out its preference level as antioxidant source. The method used in this research consisted of five steps, namely 1) makinginstant drinking powder of mangosteen peel (Garcinia mangostana L), 2) antioxidantcontent testing, 3) water content testing, 4) sugar content testing, 5) organoleptictesting. The result of the research on the antioxidant content of sample instantmangosteen peel drinking powder repeated twice with the average of 80 g of peel masswas 27.8350%, with the average 100 g of peel mass is 29.1237%, and with 120 g of peelmass was 31.7859%. Based on the result of organoleptic testing, most of therespondents preferred the sample with 120 g of the peel in terms of the taste, color,texture, and aroma. Keyword: mangosteen peel, antioxidant, drinking powder